FRI0051 Comparison Between Clinical and Ultrasonographical Examination in Early Rheumatoid Arthritis Patients. (9th June 2015) - Addimanda, O.; Macchioni, P.; Caruso, A.; Possemato, N.; Catanoso, M.G.; Boiardi, L.; Salvarani, C.
Abstract : Objectives: To stress the need of routine use of US imaging in treat to target strategies aiming to achieve remission in early rheumatoid arthritis. Methods: 72 patients consecutive with early rheumatoid arthritis (ERA, 50 pts) or undifferentiated arthritis (UA, 22 pts) diagnosed according to 2010 ACR/EULAR criteria were enrolled in a single center from november 2012 to June 2014. Demographic (age, gender, disease duration, body mass index - BMI-), clinical (total swollen and tender joints count, DAS28, CDAI, SDAI, Health Assessment Questionnaire, EULAR response), serological (eritrocyte sedimentation rate, C reactive protein, rheumatoid factor -RF-, antibodies anti-cyclic citrullinated peptide -CCP-) data was collected at baseline and at 6 months follow-up. Ultrasonographic (US) hand (MCP joints, PIP joints and DIP joints), wrists (intercarpic and radiocarpic joints) and feet (MTP joints, PIP and DIP joints as well as ankle joints) evaluation was performed according to OMERACT recommendations at baseline and 6 months. Results: At baseline examination the mean disease duration was 15, 5±7, 8 weeks (min – max 4 - 24), 33/72 (45.91%) were RF positive and 32/72 (43.1%) were ACPA positive. Sixty-four patients were treated with DMARDs (62.5% MTX, 25% HCQ, 13% others) and 57 patients received corticosteroids. Ten out of 72 patients (13.9%) showed radiographic erosions at baseline evaluation. At 6 months clinical evaluation 23 pts were in remission according to DAS28 criteria, 14 pts were in low disease activity, 23 in moderate disease activity and 10 pts still in high disease activity. Comparing US evaluation in the different level of disease acitivity only joint synovial PD showed a statistical significant difference (table1 ). Conclusions: At 6- months US joint and tendon examination of a consecutive series of patients with early RA only the presence of synovial joint PD were significantly reduced in patients with disease remission as compared to patients with more active disease. Disclosure of Interest: None declared